“I Felt like I Was Losing Every Day”: Women Educators’ Lived Experience of the COVID-19 Pandemic - Smith, Julia (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2023)
The covid-19 pandemic severely disrupted the education system in Canada from March 2020 throughout the 2020–21 school year. It also had disproportionate secondary effects on women in terms of unpaid care, economic loss, and poor mental health. This article explores the lived experience of women educators in the province of Alberta, drawing on interviews and focus groups with 39 educators. Findings indicate that the pandemic not only exacerbated the triple burden that women educators, in particular, bear but added additional layers of responsibility related to public health management, educating children at home, elder care responsibilities, and emotional labour. The essential role women educators fulfilled within the covid-19 response, at work and at home, cost them time, professional development opportunities, mental wellness, and the positive rewards that had drawn them to the educational field. Current concerns around educator burnout and retention may be mitigated by acting on the recommendations of women educators regarding the development of more equitable education systems and social policy.